1995
DOI: 10.1080/15287399509531982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of uncertainty factors in deriving RfDS for some chlorinated compounds

Abstract: Risk assessment of exposure to chemicals having a toxic endpoint routinely uses the reference dose (RfD) approach based on uncertainty factors of 10. The purpose of this investigation was to evaluate whether the magnitude of the U.S. Environmental Protection Agency (EPA) 10x uncertainty factors has scientific merit when compared with data from recent human and animal experimental studies. A compilation and comparison of ratios between LOAEL/NOAEL (lowest observed adverse effect level/no observed adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…As with other organophosphate compounds, the principal mechanism of action for chlorpyrifos is inhibition of acetylcholinesterase in mice, rats, dogs, and humans (McCollister, et al, 1974;Deacon et al, 1980;Nolan et al, 1984a;Young, Szabo, and Grandjean, 1990). It is also interesting that for oral chronic exposure to chlorpyrifos, the NOAEL ratio (for acetylcholinesterase inhibition) between animals and humans was 3.3 and 1 when rat and dog data were used, respectively, and not the default of 10 (Kadry, Skowronski, and Abdel-Rahman, 1995). The chronic NOAEL for mice was not available.…”
Section: Discussionmentioning
confidence: 96%
“…As with other organophosphate compounds, the principal mechanism of action for chlorpyrifos is inhibition of acetylcholinesterase in mice, rats, dogs, and humans (McCollister, et al, 1974;Deacon et al, 1980;Nolan et al, 1984a;Young, Szabo, and Grandjean, 1990). It is also interesting that for oral chronic exposure to chlorpyrifos, the NOAEL ratio (for acetylcholinesterase inhibition) between animals and humans was 3.3 and 1 when rat and dog data were used, respectively, and not the default of 10 (Kadry, Skowronski, and Abdel-Rahman, 1995). The chronic NOAEL for mice was not available.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports describe the underlying scientific basis of uncertainty factors (Zielhuis and van der Kreek, 1979;Dourson and Stara, 1983). Research has also been conducted in this area (see, for example, Calabrese, 1985;Hattis, Erdreich, and Ballew, 1987;Renwick, 1991Renwick, , 1993Dourson, Knauf, and Swartout, 1992;Calabrese, Beck, and Chappell, 1992;Lewis, 1993;Calabrese and Gilbert, 1993;Kadry, Skowronski, and Abdel-Rahman, 1995). The following reports of the workshop enhance this existing research.…”
Section: Michael L Dourson Guest Editormentioning
confidence: 88%
“…They also assumed that the underlying processes that contribute to population variability were multiplicative and that the median value of the distribution would be 3.2. Kadry et al (65) compared the LOAEL/NOAEL ratios for six chlorinated compounds and reported that 91.3% were less than or equal to 6. Similarly, Alexeef et al (66) found that the 95th percentile of the distribution of the LOAEL/NOAEL ratio was 6.3 for extrapolating from an acute inhalation LOAEL to a NOAEL for mild effects.…”
Section: Discussionmentioning
confidence: 98%